2011
DOI: 10.1042/bj20110167
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase enhances nerve-growth-factor-induced PC12 cell neuritogenesis via the p38 MAPK pathway

Abstract: Heparanase is involved in the cleavage of the HS (heparan sulfate) chain of HSPGs (HS proteoglycans) and hence participates in remodelling of the ECM (extracellular matrix) and BM (basement membrane). In the present study we have shown that NGF (nerve growth factor) promoted nuclear enrichment of EGR1 (early growth response 1), a transcription factor for heparanase, and markedly induced heparanase expression in rat adrenal pheochromocytoma (PC12) cells. K252a, an antagonist of the NGF receptor TrkA (tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
2
20
1
Order By: Relevance
“…Notably, it is supposed that there are complex relationships between HPSE and p38 MAPK pathway. Previous studies have showed HPSE may enhance three main MAPK members (including p38, ERK and JNK, solely or simultaneously) by phosphorylation 3436; certain pathophysiology processes induced by HPSE could be mediated after p38 regulation 37,38. In our study, however, the concurrent of HPSE up-regulation and sole p38 activation is a unique feature of HG induction and the mechanism for sole p38 activation is still obscure.…”
Section: Discussioncontrasting
confidence: 51%
“…Notably, it is supposed that there are complex relationships between HPSE and p38 MAPK pathway. Previous studies have showed HPSE may enhance three main MAPK members (including p38, ERK and JNK, solely or simultaneously) by phosphorylation 3436; certain pathophysiology processes induced by HPSE could be mediated after p38 regulation 37,38. In our study, however, the concurrent of HPSE up-regulation and sole p38 activation is a unique feature of HG induction and the mechanism for sole p38 activation is still obscure.…”
Section: Discussioncontrasting
confidence: 51%
“…As shown in Figure 4A, a p38 MAPK inhibitor SB203580 [26] and a JNK MAPK inhibitor SP600125 [27] suppressed phosphorylation of p38 and JNK, respectively. These results are in accord with recent reports that not only catalytic activities of p38 and JNK but also phosphorylation of these MAPKs by upstream MAPK kinases are inhibited by SB203580 [2830] and SP600125 [3133], respectively, under certain conditions. These MAPK inhibitors also suppressed activation of caspase-3/7 induced by the STS treatment (Figure 4B).…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have demonstrated that NGF activates different extracellular and intracellular signaling pathways leading to neurite outgrowth, including the PI3K/Akt and MEK/ERK pathways (18)(19)(20)(21). In the present study, treatment with TFSA led to a significant increase in the phosphorylation of Akt at Ser473.…”
Section: Discussionsupporting
confidence: 59%